Midnight Bayou - Roberts, Nora (New York : G. P. Putnam's Sons, 2001)
Declan Fitzgerald leaves his Boston law practice to restore a dilapidated mansion in the Louisiana bayou to its former splendor, but Declan soon becomes wrapped up in trying to solve the mystery behind a long-ago tragedy.
Keywords: Home ownership -- Fiction; Suspense fiction